MALDI Mass Spectrometry Imaging—Prognostic Pathways and Metabolites for Renal Cell Carcinomas - Erlmeier, Franziska; Sun, Na; Shen, Jian; Feuchtinger, Annette; Buck, Achim; Prade, Verena M.; Kunzke, Thomas; Schraml, Peter; Moch, Holger; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; et al. (Cancers, 2022)
High mass resolution matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) is a suitable method for biomarker detection for several tumor entities. Renal cell carcinoma (RCC) is the seventh most common cancer type and accounts for more than 80% of all renal tumors. Prognostic biomarkers for RCC are still missing. Therefore, we analyzed a large, multicenter cohort including the three most common RCC subtypes (clear cell RCC (ccRCC), papillary RCC (pRCC) and chromophobe RCC (chRCC)) by MALDI for prognostic biomarker detection. MALDI-Fourier-transform ion cyclotron resonance (FT-ICR)-MSI analysis was performed for renal carcinoma tissue sections from 782 patients. SPACiAL pipeline was integrated for automated co-registration of histological and molecular features. Kaplan–Meier analyses with overall survival as endpoint were executed to determine the metabolic features associated with clinical outcome. We detected several pathways and metabolites with prognostic power for RCC in general and also for different RCC subtypes.
CRIS-Team Scopus Importer:2022-04-15
Keywords: chromophobe renal cell carcinoma; clear-cell renal cell carcinoma; mass spectrometry imaging; metabolomics; papillary renal cell carcinoma